Perfomance evaluation of a direct injection engine using different blends of soybean (Glycine max) methyl biodiesel - Nietiedt,Gustavo H. (2011)
Diesel fuel is used widely in Brazil and worldwide. On the other hand, the growing environmental awareness leads to a greater demand for renewable energy resources. Thus, this study aimed to evaluate the use of different blends of soybean (Glycine max) methyl biodiesel and diesel in an ignition compression engine with direct injection fuel. The tests were performed on an electric eddy current dynamometer, using the blends B10, B50 and B100, with 10; 50 e 100% of biodiesel, respectively, in comparison to the commercial diesel B5, with 5% of biodiesel added to the fossil diesel. The engine performance was analyzed trough the tractor power take off (PTO) for each fuel, and the best results obtained for the power and the specific fuel consumption, respectively, were: B5 (44.62 kW; 234.87 g kW-1 h-1); B10 (44.73 kW; 233.78 g kW-1 h-1); B50 (44.11 kW; 250.40 g kW-1 h-1) e B100 (43.40 kW; 263.63 g kW-1 h-1). The best performance occurred with the use of B5 and B10 fuel, without significant differences between these blends. The B100 fuel showed significant differences compared to the other fuels.